2010
DOI: 10.1007/s12665-010-0709-x
|View full text |Cite
|
Sign up to set email alerts
|

Surface and groundwater quality characterization of Deoria District, Ganga Plain, India

Abstract: A water quality investigation was carried out in the Deoria district, Ganga plain, to assess the suitability of surface and groundwaters for domestic, agricultural, and industrial purposes. As much as 50 representative samples from river and groundwater were collected from various stations to monitor the water chemistry of various ions, comprising Ca 2? , Mg 2? , Na ? , K ? , HCO 3 -, SO 4 2-, NO 3 -, Cl -, F -, and trace metals, such as Fe, Cu, Mn, Zn, Cd, and Pb. The results showed that electrical conductanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…Shand (1952) indicated that residual water contained in pores of granites or within the crystals of rocks may contain chloride. Chloride is higher (1010 mg/L in Bederelli village) due to leaching of upper soil layers by industrial and domestic activities and dry climates; furthermore, higher concentration of Cl − in drinking water causes a salty taste and has a laxative effect in people not accustomed to it (Bhardwaj and Singh 2011). The sulfate concentration of the groundwater samples of the study area ranges from 2.5 to 375 mg/L with an average value of 56.985 mg/L, which is below the permissible limit of 400 mg/L (WHO 1990).…”
Section: Chloride (Cl − ) and Sulfate (So 4 2− )mentioning
confidence: 99%
“…Shand (1952) indicated that residual water contained in pores of granites or within the crystals of rocks may contain chloride. Chloride is higher (1010 mg/L in Bederelli village) due to leaching of upper soil layers by industrial and domestic activities and dry climates; furthermore, higher concentration of Cl − in drinking water causes a salty taste and has a laxative effect in people not accustomed to it (Bhardwaj and Singh 2011). The sulfate concentration of the groundwater samples of the study area ranges from 2.5 to 375 mg/L with an average value of 56.985 mg/L, which is below the permissible limit of 400 mg/L (WHO 1990).…”
Section: Chloride (Cl − ) and Sulfate (So 4 2− )mentioning
confidence: 99%
“…The WHO (2004) standards for drinking purposes have been considered for the calculation of DWQI. The physical and chemical parameters of pH, TDS, TH, Ca, Mg, Na, K, HCO 3 , CO 3 Cl, SO 4 , NO 3 and F were utilized. Each of 13 parameters has been assigned a weight (w i ) according to its relative importance in the overall quality of water for drinking purposes ( Table 2).…”
Section: Drinking Water Quality Index (Dwqi)mentioning
confidence: 99%
“…Recently various researchers have carried out groundwater study for drinking and irrigation water standards using different indices and plots (Rao and Rao 2010;Rao et al 2012;Bhardwaj and Sen Singh 2011;Prasanna et al 2011;Akbal et al 2011;Nosrati and Van Den Eeckhaut 2012;Sharma et al 2012;Gupta et al 2012). Besides these, Machender et al (2013) have carried out groundwater and surface water study in a Chinnearu river basin to distinguish the groundwater and surface water for drinking and irrigation use.…”
Section: Introductionmentioning
confidence: 99%